Music Therapy as Nursing Intervention in Improving Postpartum Mothers Comfort - Diffa Risqa Arisdiani; Anggorowati Anggorowati; Elsa Naviati (Media Keperawatan Indonesia, 2021)
Postpartum is a condition in which the reproductive organs return to normal which takes 6 weeks. The feeling of discomfort in postpartum mothers occurs because of the sensation of pain that is often complained of. One way to increase comfort for postpartum mothers is by providing non-pharmacological therapies, namely massage and listening to music. Music can provide impulses or stimuli that can override the pain signals. The literature review aims to describe the type of music that can increase the comfort of postpartum mothers. The method used is a literature review study. The database used from several journals and articles with a search process through Pubmed, Proquest, Springlink, Scopus, Google Scholar. The criteria for inclusion in this search were the year the articles were published, starting from 2010 to 2020. The type of classical music that has a medical connection is Mozart's music. Mozart music with a frequency of 40-60 Hz, tempo 60-80 bpm. Music therapy is given for approximately 20-30 minutes to produce a therapeutic effect with a period of twice a day for 2 days using headphones. Music used to increase comfort and reduce the anxiety that has a slow tempo, notes that are not too high or too low, has a low volume and is rhythmic with a simple arrangement, and a stable melody. The provision of music therapy, especially Mozart adagio classical music, affects reducing anxiety levels and reducing pain intensity so that it can provide a sense of comfort to postpartum mothers.